Research on Oblique Penetration of Projectiles into Targets of Different Materials. Issue 1 (August 2021) - Zhang, Xiaojing; Yao, Wenjin; Li, Wenbin; Wang, Xiaoming; Zhu, Xintao
Abstract: In order to study the trajectory deflection of projectile penetrating obliquely into different materials, the Lagrange algorithm of LS-DYNA was used to simulate the three-dimensional model. The impact angle of projectile is 70°, the concrete target and the soil target are penetrated respectively. The state of the target, the strain nephogram and the stress nephogram of the target under the maximum overload are obtained. The curves of penetration depth, penetration velocity, overload and energy are analyzed. The results show that: in oblique penetration, the projectile's trajectory deflects more in the process of entering the concrete target, and then deflects less; the trajectory deflection of the projectile is small in the process of entering the soil target and a certain distance after it, but it becomes larger when it is fast out of the target.